Factors That Affecting Customer Intention To Use Telemedicine Applications Continuously After Covid-19 Pandemic In Indonesia - Fandika, Gilang; Kusumawati, Nurrani (Integrasi Sains Media, 2023)
During the COVID-19 Pandemic, telemedicine has had a high use rate since the government issued a policy limiting people's movement to reduce transmission. It is because telemedicine can be a way to solve this issue since it can provide and support health care when distance separates the users only using electronic communication technologies. However, through this remote assessment, patients and physicians lose the opportunity to interact in person, which might impact doctor-patient communication. Furthermore, covid-19 cases in Indonesia have shown a downward trend, making the government have no regulation limiting people's movement. Now, people can see their physicians directly for some conditions. Therefore, this research will analyze factors influencing customer intention to consult through telemedicine applications and determine which factors more significantly influence customer intention. This research is conducted through a qualitative approach by semi-structured interviews and a quantitative approach by an online survey of customers who ever experience using telemedicine applications. The researcher uses open coding to analyze the interview result and descriptive statistics and PLS-SEM to analyze the survey result. The author gets seven respondents from interviews and 317 from online surveys. The results indicate that perceived benefit, satisfaction, saving time, saving cost, and performance expectancy influence customer intention to use telemedicine applications continuously. Furthermore, satisfaction and saving costs are the factors that significantly influence customer intention to use telemedicine applications continuously. The finding of this research is expected to give insight into telemedicine applications in Indonesia about making their strategies to enhance their customer intention to use continuously.